The link between neuroinflammation and the neurovascular unit in synucleinopathies - Wang, Qing; Zheng, Jialing; Pettersson, Sven *; Reynolds, Richard; Tan, Eng-King (American Association for the Advancement of Science, 2023)
The neurovascular unit (NVU) is composed of vascular cells, glial cells, and neurons. As a fundamental functional module in the central nervous system, the NVU maintains homeostasis in the microenvironment and the integrity of the blood-brain barrier. Disruption of the NVU and interactions among its components are involved in the pathophysiology of synucleinopathies, which are characterized by the pathological accumulation of α-synuclein. Neuroinflammation contributes to the pathophysiology of synucleinopathies, including Parkinson’s disease, multiple system atrophy, and dementia with Lewy bodies. This review aims to summarize the neuroinflammatory response of glial cells and vascular cells in the NVU. We also review neuroinflammation in the context of the cross-talk between glial cells and vascular cells, between glial cells and pericytes, and between microglia and astroglia. Last, we discuss how α-synuclein affects neuroinflammation and how neuroinflammation influences the aggregation and spread of α-synuclein and analyze different properties of α-synuclein in synucleinopathies.